2017
DOI: 10.1038/s41598-017-01624-4
|View full text |Cite
|
Sign up to set email alerts
|

DNA methylation and Transcriptome Changes Associated with Cisplatin Resistance in Ovarian Cancer

Abstract: High-grade serous ovarian cancer is the most common ovarian cancer type. Although the combination of surgery and platinum-taxane chemotherapy provide an effective treatment, drug resistance frequently occurs leading to poor outcome. In order to clarify the molecular mechanisms of drug resistance, the DNA methylation and transcriptomic changes, associated with the development of drug resistance in high-grade serous ovarian cancer, were examined from patient derived malignant ascites cells. In parallel with larg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(54 citation statements)
references
References 48 publications
0
49
0
Order By: Relevance
“…Chemotherapy sensitivity may be due to changes in gene expression caused by epigenetic changes such as DNA methylation at the promoter after treatment 18 . Methylation at promoters has been reported to play an important role in regulating LCN2 expression 17 .…”
Section: Lcn2 Was Up-regulated After Cisplatin Treatment and Down-regmentioning
confidence: 99%
“…Chemotherapy sensitivity may be due to changes in gene expression caused by epigenetic changes such as DNA methylation at the promoter after treatment 18 . Methylation at promoters has been reported to play an important role in regulating LCN2 expression 17 .…”
Section: Lcn2 Was Up-regulated After Cisplatin Treatment and Down-regmentioning
confidence: 99%
“…Resistance/sensitization Genes Cisplatin resistance OXCT1 [18] , GPCR [19] , TET1 [20] , MLH1 [21][22][23] , HOXA10, HOXA11 [21,24] , NAGA [25] , UCHL1 [26] , BCL2L1 [27] , FANCF [28][29][30] Cisplatin sensitization FANCF [31] , NAGA [25] , CCDC69 [32] , UCHL1 [26] Carboplatin Resistance TMEM88 [33] , DOK2 [34,35] , p57(Kip2) [36] , Plk2 [37] , HERV-K [38] , SFRP5 [39] , SLFN11 [40] , ASS1 [41] ASS1: argininosuccinate synthase 1; BCL2L1: BCL2 like 1; CCDC69: coiled-coil domain containing 69; DOK2: docking protein 2; FANCF: fanconi anemia complementation group F; GPCR: protein coupled receptor; HOXA: homeobox A cluster; HERV-K: for HERV-K: human endogenous retrovirus type K; MLH1: mutL homolog 1; NAGA: N-acetylgalactosaminidase; OXCT1: 3-oxoacid CoA-transferase 1; Plk2: polo like kinase 2; SFRP5: secreted frizzled-related protein 5; SLFN11: schlafen family member 11; TET1: tet methylcytosine dioxygenase 1; TMEM88: transmembrane protein 88; UCHL1: ubiquitin C-terminal hydrolase L1 β-catenin independent (non-canonical) pathways. Wnt proteins bind to receptors of the Frizzled and the low-density lipoprotein receptor-related protein families on the cell surface.…”
Section: Table 2 Epigenetically Modifiable Genes Relevant To Ovarianmentioning
confidence: 99%
“…A study from 2017 also suggests that hypomethylation can be induced by cisplatin treatment in resistant OC patients, however loss of methylation was primarily observed in intergenic regions (109). Other recent studies have suggested a correlation between hypomethylation of developmental genes and platinum resistance in OC patients.…”
Section: Dna Methylation and The Prediction Of Chemo-resistancementioning
confidence: 98%